Ecobiology of Asian-moon Scallop Amusium pleuronectes (Linnaeus, 1758) in Kendal Regency Coast, Central Java - Satriawan, Erian Febri; Suryono, Chrisna Adhi; Widowati, Ita; Saputri, Mimie (Universitas Diponegoro, 2024)
Asian moon scallops are one of the marine biological resource products that have the potential to be utilized optimally and in national and international trade and have high economic value. Kendal waters are one of the districts with significant Amusium pleuronectes resource potential to meet export needs in Indonesia, apart from the waters of Brebes, Tegal, Pemalang, Pekalongan, and Batang regencies. This research aims descriptively to explain the habitat characteristics of A. pleuronectes by connecting the condition of the relationship between body size and weight of A. pleuronectes and the parameters quality of the waters where the scallops are located, based on fishermen's fishing ground routes. A. pleuronectes was sampled using a fishing boat with a traditional arad net. The Global Positioning System (GPS) would be turned on when the arad net was finished being lifted, and the coordinates were recorded. The sampling stations were determined as 4 points, spread randomly (purposive sampling) along the route of fishermen catching A. pleuronectes. At the same time, water, sediment, and water parameter sampling was carried out. The samples were then taken to the laboratory for biometric measurements to determine the condition of the A. pleuronectes. Water samples were tested for chlorophyll-a and nitrate content, while sediment was tested for grain size and organic matter content. A Principal Component Analysis (PCA) analysis was conducted to determine the relationship between biometric parameters and water parameters. The results of this study showed that the scallops have a relationship between size and weight x<3, so they have negative allometry. These scallops have an average condition index of 51.12 and are in the medium category. In the preliminary survey, these scallops were dominated by the 4.1-5 cm size class. At stations 1-3, the size class 6.1-7 cm is dominated. A. pleuronectes were not found at station 4. These scallops showed a close relationship with salinity, depth, nitrate content, and silt substrate, with a higher content of coarse sand and clay as a substrate. There is little relation to organic matter, chlorophyll-a, temperature, dissolved oxygen, pH, gravel substrate, silt, and fine sand.